SISTEM PAKAR MENDIAGNOSA PENYAKIT PADA BURUNG LOVEBIRD DENGAN METODE FORWARD CHAINING BERBASIS WEB - Manurung, Efran Louis; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2025)
The disease known as avian pox poses a serious threat to Lovebirds and can lead to their death. In some regions, this illness is referred to as